Narrative Review: Risk-Benefit Hydroxychloroquine and Chloroquine in COVID-19 - Jarir At Thobari (Universitas Gadjah Mada, 2021)
Chloroquine (CQ) and Hydroxychloroquine (HCQ) are highly prescribed as medications for COVID-19 infection, although no robust or convincing data has yet been published about the efficacy in COVID-19 patients. Therefore, risk and benefit assessment are necessary for decision to prescribe these drugs in COVID-19 patient in hospitals settings. We systematically searched from MEDLINE Database which investigate the benefits and risks of HCQ and CQ among COVID-19 patients. All records were searched using the search terms Hydroxychloroquine, Chloroquine, COVID-19, and SARS-CoV-2. The selection criteria include all clinical trials and observational studies. We found 11 records about benefit and 7 records about risks on HCQ and CQ in COVID-19 patients after following inclusion and exclusion criteria. From clinical trial and observational studies have showed that HCQ is very limited benefit particularly on reduction of mortality or clinical improvement. Similarly, there were seven observational studies have estimated the cardiac event in use of HCQ or CQ in COVID-19. Even though no increase death, but these studies reported the increase risk of prolong QT-interval in high proportion and other cardiac events such as arrythmia, torsade de pointes and conduction block. We conclude that the benefit effect of HCQ and CQ in COVID-19 remains very limited. However, both medications have independently shown to increase the risk in other populations for QT-interval prolongation, drug-induced torsades de pointes/TDP (a form of polymorphic ventricular tachycardia) and drug-induced other cardiac events.